An Ecofeminist Analysis of the Lyrics of Colours of the Wind in Disney’s Pocahontas (1995) - Poetry Salsabila Nurrania; Bugi Gustaman (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
This study examines the lyrics of “Colors of the Wind” from Disney’s animated film Pocahontas (1995) as a discursive site of resistance to colonial paradigms. Performed by Judy Kuhn, the song serves as a pivotal focalization of Pocahontas’s Indigenous wisdom in opposition to Western expansionism. The research investigates how the lyrics construct colonial settlers as “alien” subjects who are ecologically estranged while simultaneously articulating an alternative human–nature relationship grounded in an ecofeminist ethics of care. Employing ecofeminist literary criticism, the study analyzes the lyrics through a close reading informed by the conceptual frameworks of the logic of domination, master identity, and the mechanistic death-of-nature paradigm. The findings reveal that colonial figures are represented as “aliens” through processes of othering and a mechanistic worldview that reduces the Earth to a “dead thing” or a mere object of exploitation. Their inability to comprehend the language of nature reveals a profound ontological disconnection from local ecological networks, effectively rendering them outsiders within the very environment they seek to conquer. In contrast, Pocahontas’s voice rearticulates nature as a living entity, foregrounding a circular model of interconnectedness as a counter-discourse to linear and anthropocentric colonial hierarchies. The study concludes that the settlers’ status as “aliens” is an ideological consequence of the colonizers’ master identity, which rejects ecological relationality. Ultimately, the study underscores the vital contribution of ecofeminist readings of popular culture to critiques of the colonial and patriarchal logics that continue to underlie contemporary ecological crises.